Improving Beginning Reading Skills of Foreign Learners through Repetition Theory: A Case Study of BIPA Learners at Thammasat Wittaya, Thailand - Anjani, Desi; Febriyana, Mutia (Journal of English Language and Education, 2025)
This study explores the effectiveness of applying repetition theory to enhance beginning reading skills among foreign learners at Thammasat Wittaya School in Thailand. Using a descriptive qualitative approach, this classroom action research involved 15 Matthayom 2 students over one month in August 2024. Data were collected through observation, interviews, and documentation. The study focused on five assessment criteria: accuracy of voicing and writing, pronunciation fairness, intonation fairness, fluency, and clarity of voice. The results indicate that repetition theory positively impacts learners’ reading abilities, with significant variation in performance among students. Some learners showed consistent improvement, while others required more intensive support. such as Nunchaona getting 18, Sadeen getting 17, Najwa getting 16, and Chanapa getting 16, showing consistent good performance in all aspects of the assessment. On the other hand, learners like Nisna got 7, Nadir got 7, and Nur got 10. These learners need more intensive guidance. In-depth analysis of learners' reading ability was conducted through five main aspects: accuracy of writing, pronunciation fairness, intonation fairness, fluency, and clarity of voice. The results showed significant variation in ability among learners.